Great Britain. Board of Trade records - Great Britain. Board of Trade
Volumes containing correspondence, reports, orders, instructions, commissions, and other records documenting British trade in Canada, the Caribbean, and America. Notes trade with Antigua, Bermuda, France, Jamaica, New England, Newfoundland, New Jersey, Nova Scotia, Pennsylvania, South Carolina, and Virginia. Chronicles British trade decisions and actions concerning fishing, shipping, and whaling, and trade disputes with Spain.
British government agency established to promote and regulate British overseas commerce.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Fishing; Shipping; Whaling; America -- Commerce -- Great Britain; Antigua -- Commerce -- Great Britain; Bermuda Islands -- Commerce -- Great Britain; Canada -- Commerce -- Great Britain; Caribbean Area -- Commerce -- Great Britain; France -- Commerce -- Great Britain; Jamaica -- Commerce -- Great Britain; New England -- Commerce -- Great Britain; Newfoundland -- Commerce -- Great Britain; Nova Scotia -- Commerce -- Great Britain; Pennsylvania -- Commerce -- Great Britain; New Jersey -- Commerce -- Great Britain; South Carolina -- Commerce -- Great Britain; Spain -- Commerce -- Great Britain; Virginia -- Commerce -- Great Britain; Great Britain -- Commerce; Great Britain -- Commerce -- America; Great Britain -- Commerce -- Antigua and Barbuda -- Antigua; Great Britain -- Commerce -- Bermuda Islands; Great Britain -- Commerce -- Canada; Great Britain -- Commerce -- Caribbean Area; Great Britain -- Commerce -- France; Great Britain -- Commerce -- Jamaica; Great Britain -- Commerce -- New England; Great Britain -- Commerce -- Newfoundland; Great Britain -- Commerce -- New Jersey; Great Britain -- Commerce -- Nova Scotia; Great Britain -- Commerce -- Pennsylvania; Great Britain -- Commerce -- South Carolina; Great Britain -- Commerce -- Spain; Great Britain -- Commerce -- Virginia